İşyeri devrinin iş sözleşmelerine etkisi ve işverenlerin hukuki sorumluluğu - Özkaraca, Ercüment (My University, 2008)
İşyeri devri işçilerin iş ve gelir güvencesi açısından yaşamsal öneme sahiptir. İşyeri devrinin iş sözleşmelerine etkisi, Avrupa Birliğine üye ülkelerde çok sayıda bilimsel incelemeye ve mahkeme kararlarına konu olmuştur. Konuyu özel olarak düzenleyen bir AB Yönergesi de mevcuttur. Hukukumuzda işyeri devri İş Kanununun 6. maddesinde düzenlenmiştir. İşyerinin devri halinde iş sözleşmeleri kendiliğinden devralan işverenle devam etmekte ve devralan işveren işçinin hizmet süresinin esas alındığı haklarda işçinin devreden işveren yanında işe başladığı tarihe göre işlem yapmakla yükümlü olmaktadır. İşçilerin devir tarihinde muaccel olan alacaklarından devreden ve devralan işveren birlikte sorumludur. Ancak devreden işverenin sorumluluğu devir tarihinden itibaren iki yılla sınırlıdır. Devreden veya devralan işveren iş sözleşmesini sırf işyerinin veya işyerinin bir bölümünün devrinden dolayı feshedemez ve devir işçi yönünden fesih için haklı sebep oluşturmaz. Devreden veya devralan işverenin ekonomik ve teknolojik sebeplerin yahut iş organizasyonu değişikliğinin gerekli kıldığı fesih hakları veya işçi ve işverenlerin haklı sebeplerden derhal fesih hakları saklıdır. İflas dolayısıyla malvarlığının tasfiyesi sonucu işyerinin devri halinde ise Kanunda öngörülen düzenlemeler uygulanmamaktadır. Hukukumuzda öngörülen bu düzenlemeler genel olarak isabetli olmakla birlikte, Avrupa Birliği müktesebatına uyum açısından, işyeri devrinde bilgi verme ve danışma yükümlülüğü öngörülmeli ve işçiye itiraz hakkı tanınmalıdır. Ayrıca devreden işverenin sorumluluğu için öngörülen iki yıllık süre sınırı kaldırılmalıdır. İşçilerin kazanılmış haklarının korunması açısından iflas durumunda öngörülen istisna hükmünün de yumuşatılması gereklidir.

The transfer of an establishment carries vital importance for employees in means of employment and income security. The impact of transfer of establishment on the employment contracts has been subject of numerous academic studies and court decisions at European Union Countries. There is an European Union directive which regulates this issue privately. The transfer of an establishment is regulated by our Law at article 6 of the Turkish Labour Code. In case of an establishment transfer, the employment contract automatically continius to be valid with the transferee and the transferee is bound to proceed according to the date the employee has started working for the transferror as for the rights that are linked to the working period of the employee. The transferror and the transferee are jointly liable for the employee claims due at the date of transfer. On the other hand the liability of the transferror is limited with 2 years starting from the transfer of the establishment. Neither transferror, nor transfree is entitled to terminate the employment agreement because of the transfer of establishment or a section thereof. The transfer of the employment does not constitute a “just cause” for employee in order to terminate the agreement too. This does not prejudice the transferors’s and transferee’s rights to terminate the employment agreement due to economic and technological reasons and organisational changes. This also does not prejudice employers’ and employees’ right to terminate the employment agreements on “just causes”. These provisions do not apply in case the transfer of the establishment is as a result of liquidation of the employer’s assets due to insolvency of the employer. Although the above mentioned regulation of our Law is appropriate, the right of employee to reject shall be recognized and the obligation to give information and to consult shall be regulated for establishment transfers in order to provide harmony with the acquis communitaire. Moreover, the transferror’s two years time limitation for liability shall be removed. Finally the exceptional provision prescribed for the cases of insolvency shall be diminished in order to protect the employees’ acquired rights.
Keywords: Hukuk; İş Hukuku; İş Sözleşmeleri; Özel Hukuk